NITROIMIDAZOLES IV [I]. SYNTHESIS OF 3,s-DICARBO ALKOXY-2,6-DIMETHYL-4-(1 -METHYL-5- NITRO-2-1MIDAZOLYL)-1,4-DIHYDROPYRIDIANNE D 3,5-DICARBOALKOXY- 2,6-DIMETHYL-4(-2 -S UBSTI - TUTED-4-THIAZOLYL)-l , 4- DIHYDROPYRIDINE (Journal of Sciences, Islamic Republic of Iran)
Different procedures for the syntheses of the title compounds were investigated. The best method for the preparation of the title compounds were the reaction of the readily available 2-formyL-1-methyl-5-nitroimidazole2- substituted-4-formylthiazoles with alkyl acetoacetate and alkyl aminocrotonate in boiling alcohol.